Development of Kramat Tunggak Localization (1966-1971) - Aprilianto, Muhammad Bagus; Siswantari, Siswantari (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The problem of prostitution in Jakarta which was increasingly widespread and uncontrolled in the 1960s encouraged the emergence of the idea to build a localization in the Kramat Tunggak area, North Jakarta. In the process of realizing this idea, various dynamics occurred that influenced the development of Kramat Tunggak as the first localization built by the Jakarta government. This article aims to explain the dynamics in the development of the Kramat Tunggak Localization during 1966-1971. Through historical research methods and a structuralist approach by Christopher Lloyd, this article will discuss starting from how prostitution developed in the North Jakarta area in the 1960s, what was the purpose of Ali Sadikin in initiating the development of the localization and why Kramat Tunggak was chosen as the area for the establishment of the Jakarta localization and how the implementation process of Kramat Tunggak as the first localization in the Jakarta area. In this study, it was concluded that the establishment of the Kramat Tunggak Localization not only gave rise to pros and cons in society, but after the completion of the Kramat Tunggak Localization, it encouraged the growth of settlements, infrastructure and economic activities of the community around the localization and succeeded in localizing prostitution practices in Jakarta.